The roles of strategic management accounting on heterogeneity of human capital, information technology capabilities and value creation / Nik Herda Nik Abdullah - Nik Abdullah, Nik Herda (Faculty of Accountancy, 2019)
This study investigates the effectiveness of strategic management accounting practices (SMA) in enhancing the relationship between heterogeneity of human capital, information technology capabilities and value creation in Malaysian Government Linked Companies (GLCs). The lack of value creation and structural capabilities create a gap in talent, execution skills and capabilities, which are the challenges commonly faced by GLCs. At present, studies that emphasise the role of SMA practices in promoting value creation and internal capabilities are not widely available. Through structural equation modelling and analyses of data collected from 215 questionnaires, the findings appear to support the roles of SMA practices in enhancing the relationship heterogeneity of human capital and information technology capabilities on value creation in GLCs. These results extend to the growing body of knowledge on SMA practices, value creation and dynamic capabilities theory specifically on heterogeneity of human capital and information technology capabilities. Besides, it serves as a base for future studies on SMA. In addition, this study highlights the adoption of SMA practices that promotes value creation in GLCs by facilitating to improve competitiveness in the industry, upgrade financial standings, create avenues for gaining profit, business sustainability and long-term performance. However, this study is subjected to its own limitations such as generalisation, research design and literature, which could be overcome in future research.